Expression of goat poxvirus P32 protein and monoclonal antibody preparation - Liu, Ying; Wang, Lei; Chen, Xiaoyun; Ma, Xin; Yin, Chunsheng; Yang, Chenghuai; Liu, Bo; Du, Jige (Frontiers in Cellular and Infection Microbiology, 2024)
P32 protein serves as a crucial structural component of Goat pox virus (GTPV), which causes a highly virulent infectious disease in sheep and goats. Despite the fact that P32 has been widely expressed in the previous studies, it is difficult to obtain recombinant P32 efficiently. This study aimed to achieve soluble expression of P32 recombinant protein and to develop its specific monoclonal antibody. The gene fragment of P32Δ (GP32Δ) was synthesized by optimizing the coding sequence of amino acids 1-246 of the known goatpox P32 protein. Subsequently, GP32Δ was cloned into a prokaryotic expression vector for expression and purification, resulting in the successful production of soluble recombinant protein rP32Δ. Utilizing rP32Δ, an indirect ELISA method was established by immunizing 6-week-old BALB/c mice with inactivated GTPV as the antigen. Through hybridoma technology, three monoclonal antibody hybridoma cell lines secreting anti-goat pox virus rP32Δ were screened, designated as 2F3, 3E8, and 4H5, respectively. These monoclonal antibodies, classified as IgG1, IgG2a, and IgG2b, respectively, with κappa light chains, were characterized following ascites preparation and purification. Indirect ELISA results demonstrated that the ELISA potency of the three monoclonal antibodies exceeded 1:12800. Furthermore, Western blot analysis revealed specific reactivity of both 3E8 and 4H5 with rP32Δ, while immunofluorescence assays confirmed 3E8's ability to specifically recognize GTPV in cells. The preceding findings demonstrate the successful acquisition of the soluble expressed recombinant P32 protein and its specific monoclonal antibody 3E8 in this study, thereby laying a foundational material basis for the establishment of a GTPV detection method.